Bench-stable imine surrogates for the one-pot and catalytic asymmetric synthesis of α-amino esters/ketones. Issue 91 (29th October 2020) - Xu, Huacheng; Nazli, Adila; Zou, Cheng; Wang, Zhi-Peng; He, Yun
Abstract : An unpresented catalytic asymmetric method for the synthesis of α-amino esters and ketones from novel imine surrogates is reported. Abstract : N, O -Bis( tert -butoxycarbonyl)hydroxylamines are readily accessible as imine surrogates, which are bench stable and could quantitatively generate the corresponding imines for in situ applications. An unpresented catalytic asymmetric method for the synthesis of α-amino esters and ketones from novel imine surrogates, N, O -bis( tert -butoxycarbonyl)hydroxylamines, as well as its preliminary mechanistic studies are reported. A variety of optically enriched products were obtained in excellent yields and enantioselectivities (up to 99% yield and >99% ee).